2010
DOI: 10.3354/meps08630
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries yield and primary productivity in large marine ecosystems

Abstract: Primary productivity (PP) and fisheries yield were analysed in 14 large marine ecosystems (LMEs), which encompassed temperate boreal shelves and the Eastern Boundary Currents (EBCs), from 1998 to 2002. PP was estimated by means of a depth-integrated neural network model based on Sea-viewing Wide Field-of-view Sensor (SeaWiFS) data and aimed at providing conservative PP estimates. Landings records were extracted from the global spatial database provided by the Sea Around Us Project (SAUP). Correspondence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 40 publications
(86 reference statements)
2
39
0
Order By: Relevance
“…The blending of empiricism and mechanistic principles applied in this study is intended to help bridge the gap between predominantly data-driven analysis of catch indicators (14,15,19) and the development and application of more mechanistic global fisheries models rooted in theoretical constraints but of often challenging complexity (13,(62)(63)(64)(65). Parameters and emergent patterns from the simple trophodynamic models herein can be directly compared against simulated patterns from these latter models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blending of empiricism and mechanistic principles applied in this study is intended to help bridge the gap between predominantly data-driven analysis of catch indicators (14,15,19) and the development and application of more mechanistic global fisheries models rooted in theoretical constraints but of often challenging complexity (13,(62)(63)(64)(65). Parameters and emergent patterns from the simple trophodynamic models herein can be directly compared against simulated patterns from these latter models.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges have led many to forgo explicit trophodynamic approaches to understand catch constraints in favor of exploring correlations with diverse oceanographic indicators, such as average chlorophyll and variability, the presence or strength of fronts, ecosystem size, and dispersal properties (14)(15)(16)(17)(18). Others have included subsets of trophodynamic factors within large multifactor regressions (19,20).…”
mentioning
confidence: 99%
“…The contribution of diatoms (a group of large-sized and nutritious (or palatable) phytoplankton) to primary production generally increases with total production (Chisholm 1992), favouring the efficient and relatively direct transfer (i.e., involving few feeding steps) of photosynthetically fixed organic matter to top predators and, if applicable, commercial fish stocks (Conti and Scardi 2010;Cushing 1989). In the most productive upwelling regions, the direct consumption of large-sized diatoms by large zooplankton and fish leads to high ecological efficiency and high fisheries yields.…”
Section: Size or Species Compositionmentioning
confidence: 99%
“…A recent review indicated that fisheries yield and the average trophic level (TL) of catches are related to the extent of intra-annual temporal variability in PP across Large Marine Ecosystems (Conti and Scardi 2010). The TL of the catch ranges from~2.7 for small pelagic fish with a mixed diet of phytoplankton and zooplankton, to~3.8 for demersal fish feeding primarily on smaller fish and large invertebrates.…”
Section: Timing Of Ice-algal and Pelagic Productionmentioning
confidence: 99%
See 1 more Smart Citation